(untitled) (Acta Scientiarum. Agronomy, 2019)
Given the high demand for food worldwide, options for maximizing food production with minimum environmental impact are needed. Therefore, the objective of the present study was to evaluate the effect of silicon (Si) and methyl jasmonate (MeJA) in the vegetative development and genetic stability of rice plants, BRSMG Caravera cultivar. The treatments used were T1 - Control group (without Si and MeJA); T2 - Tween foliar; and T3 - Si drench, T4 - MeJA foliar, and T5 - Si drench + MeJA foliar. The use of Si or Si + MeJA promoted an increase in the height, relative chlorophyll index (RCI), and fresh and dry masses, in addition to a greater Si accumulation in the plants. However, there was no difference in the quantity of DNA or in the coefficient of variation (CV) among the treatments, proving the use of silicon separately or in combination with methyl jasmonate contributed to the vegetative development and did not affect the genetic stability of the plants.